Inhibition of IKKβ/NF-κB signaling facilitates tendinopathy healing by rejuvenating inflamm-aging induced tendon-derived stem/progenitor cell senescence - Chongyang Wang; Zhekun Zhou; Wei Song; Zhuochang Cai; Zhenyu Ding; Daoyun Chen; Fangfang Xia; Yaohua He (Elsevier, 2022)
Degenerative rotator cuff tendinopathy (RCT) is a chronic tendon disease caused by degeneration and inflammation, which often affects the elderly population. Mesenchymal stem cell senescence is generally recognized as an important pathophysiological mechanism in many age-related skeletal diseases. Herein, we collected human tendon-derived stem/progenitor cells (TSPCs) from degenerative supraspinatus tendons and found that TSPC senescence is closely related to RCT. We further identified that nuclear factor κB (NF-κB) pathway activation is involved in age-related inflammation (inflamm-aging) of degenerative RCT. Moreover, whole genome RNA sequencing revealed that in vitro inhibition of the I kappa B kinase β (IKKβ)/NF-κB signaling pathway could reverse the aged TSPC phenotype with decreased TSPC senescence and increased tenogenic potential. To achieve effective in vivo inhibition of IKKβ/NF-κB signaling, we fabricated IKKβ small interfering RNA (siRNA)-loaded gold nanoclusters (AuNC-siRNA) for efficient and convenient intra-articular delivery of IKKβ siRNA. We found that AuNC-siRNA prevented inflamm-aging-induced TSPC senescence and dysfunction in a degenerative RCT aged rat model. Together, these data show that inflamm-aging causes degenerative RCT through inducing TSPC senescence, which can be reversed by blocking the IKKβ/NF-κB pathway in vivo. Thus, our study provides a promising therapeutic strategy for degenerative RCT via intra-articular delivery of IKKβ siRNA using AuNCs.